Mapping SS1-3 chemistry teachers’ interest, self-efficacy, and literacy in teaching for creativity using simulation - Nja, Cecilia Obi; Ukwetang, John Okpa; Orim, Richard Ekonesi; Cornelius-Ukpepi, Bernedette; Ndifon, Rita Asu (Frontiers in Education, 2022)
The purpose of this article was to analyze chemistry teachers’ interest, literacy, self-efficacy, teamwork, and creativity in the use of simulation teaching of concepts in chemistry to enhance students’ creativity skills. A descriptive and exploratory quantitative design was used in the study. The study used 150 serving chemistry teachers from the Calabar education zone public education system. A 29-item questionnaire was employed to gather data from respondents. Independent t-test, regression, and a 2-way analysis of variance were used for data analysis. Results obtained indicated high levels of teachers’ interest, literacy, self-efficacy, and teamwork in the utilization of simulation strategy in teaching chemistry concepts. Results of a 2-way analysis indicated that teachers’ age and years of experience influence teachers’ self-efficacy, teamwork, and creativity. It was recommended among others that serving teachers’ interest in the use of simulation is encouraged to support their learners’ instructional activities in a simulated classroom.